Penanaman Karakter Toleransi Beragama pada Anak Usia Dini di TK Negeri Pembina Padang Lawas - Amini, Wirda Hanum; P, Fuji Rahmadi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Islam teaches many things about life, including moral education which touches on good attitudes in respecting differences between religions. Religious tolerance instilled in children from an early age will have an impact on real life in the future. The educational environment plays a significant role in teaching children the value of religious tolerance. The aim of this research is to examine forms of cultivating the character of religious tolerance in young children at the Pembina Padang Lawas State Kindergarten. This research is qualitative research with data collection techniques, namely participant observation and in-depth interviews. The results of this research state that cultivating the character of religious tolerance in early childhood is carried out with three activities, namely creating peace, respecting individual differences and building awareness. Aspects of peace include caring for others, not being afraid to defend others and loving others. The aspect of respecting individual differences includes respecting other people who are praying and carrying out worship activities in accordance with the teachings of their religion. Meanwhile, the awareness aspect includes being willing to accept suggestions and input, returning kindness to other people and being comfortable doing activities with other people. The implementation of these three activities is carried out by strengthening religious formation in the morning, cultivating prayer before and after learning, active collaboration with parents in cultivating the character of religious tolerance in children.